Cytological Grading of Chronic Lymphocytic Thyroiditis and Correlation with Thyroid Profile - Sajjan, Netra M; Vani, B R; V, Srinivasamurthy; Vijayakumari, V (Annals of Pathology and Laboratory Medicine, 2020)
Background: Chronic lymphocytic thyroiditis is a thyroid specific autoimmune disease often seen in middle aged women, although rarely do occur in men, children1. This disease is characterized by antibody directed against thyroid peroxidase, called antimicrosomal antibody. The present study was undertaken to evaluate the various cytological features occurring in HT and to correlate with clinical and serological findings. Methods: The study was conducted in department of Pathology from May 2017 to August 2017. The cases diagnosed as HT by FNAC were taken up for the study. Cytomorphologic features were reviewed microscopically and graded as per Bhatia et al. Result: Fifty cases were diagnosed as lymphocytic thyroiditis. Age of the patient ranged from 7-56 years. Clinically 41 of 50 cases (82%) presented with diffuse thyroid enlargement. In our study we had 31 cases (62 %) of grade 2 thyroiditis, 15 and 4 cases each of grade 1 and grade 3 respectively. We observed increased TSH values in 100% of G3 thyroiditis and 64.5% of G2 thyroiditis. None of the Grade 1 thyroiditis had increased TSH levels. The statistical correlation between grades of thyroiditis with T3, T4 and TSH levels was found to be significant with p values < 0.05. Conclusion: FNAC is simple cost effective and quick method for diagnosing HT. Also combined evaluation of HT with clinical findings and thyroid profile promotes more accurate diagnosis and early institution of therapy and follow up. FNAC is also necessary to rule out malignant lesions like lymphoma and papillary carcinoma at preliminary cytological level.